PENGARUH PUPUK FOSFOR DAN KALIUM TERHADAP PERTUMBUHAN DAN HASIL BENIH KENAF (Hibiscus cannabinus L.) PADA TANAH LATOSOL - Ade Wachjar; Donathus Sutidjo; Syaiful Bahri (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1994)
The experiment was aimed to study the effects of phosphorous and potassium fertilizers on growth and seed yield of kenaf on Latosol. The experiment was carried out at Tajur Experimental Station, IPB Bogor, from January 1991 to July 1991. The seed germination test was held in the Laboratory of Seed Science and Technology IPB, Bogor. Kenaf variety Hc-48 was used in this experiment. The two factor factorial experiment was arranged in Randomized Block Design with 3 replications. The first factor was 4 levels of phosphorous fertilizer: 0, 30, 60 and 90 kg P2O5/ha. The second factor was 3 levels of potassium fertilizer: 0, 60 and 120 kg K2O/ha. Phosphorous and potassium fertilization each increased significantly plant height, stem diameter, the number of mature and total fruit per plant, seed yield per hectar: however there were no significant effect on percentage of mature fruit, number of seeds per fruit, weight of 1,000 seeds and seed germination. The dosage of phosphorous fertilizer until 90 kg P2O5/ha still increased yield linearly, otherwise the optimum dosage of potassium fertilizer was reached on 69.31 kg K2O/ha with seed yield 2,036.48 kg/ha. There was no interaction effect between P and K fertilization.